A Urea Biosensor from Stacked Sol-Gel Films with Immobilized Nile Blue Chromoionophore and Urease Enzyme - Musa Ahmad; Lee Yook Heng; Muawia Salameh Alqasaimeh (Sensors, 2007)
An optical urea biosensor was fabricated by stacking several layers of sol-gelfilms. The stacking of the sol-gel films allowed the immobilization of a Nile Bluechromoionophore (ETH 5294) and urease enzyme separately without the need of anychemical attachment procedure. The absorbance response of the biosensor was monitoredat 550 nm, i.e. the deprotonation of the chromoionophore. This multi-layer sol-gel filmformat enabled higher enzyme loading in the biosensor to be achieved. The urea opticalbiosensor constructed from three layers of sol-gel films that contained urease demonstrateda much wider linear response range of up to 100 mM urea when compared with biosensorsthat constructed from 1-2 layers of films. Analysis of urea in urine samples with thisoptical urea biosensor yielded results similar to that determined by a spectrophotometricmethod using the reagent p-dimethylaminobenzaldehyde (R2 = 0.982, n = 6). The averagerecovery of urea from urine samples using this urea biosensor is approximately 103%.